A Pharmacodynamic Evaluation of the Protective Effects of Roxadustat Against Hypoxic Injury at High Altitude - Guo Q; Li X; Li W; Wang R; Zhao A; Wang Z (Dove Medical Press, 2023)
Qianwen Guo,1,2,* Xue Li,1,* Wenbin Li,1 Rong Wang,1 Anpeng Zhao,1 Zihan Wang1,2 1Pharmacy of the 940th Hospital of PLA Joint Logistics Support Force, Lanzhou, People's Republic of China; 2School of Pharmacy, Gansu University of Traditional Chinese Medicine, Lanzhou, People's Republic of China*These authors contributed equally to this workCorrespondence: Wenbin Li, Key Laboratory of the Plateau of the Environmental Damage Control, The 940th Hospital of Joint Logistics Support Force of Chinese People's Liberation Army, Lanzhou, 730050, People's Republic of China, Tel +86-931 8994654, Fax +86-931 2662722, Email yfcs2002@163.com; yjsc@gszy.edu.cnPurpose: To investigate roxadustat's preventive effects on hypoxia damage in the quick ascent to high altitude.Methods: The roxadustat (7.8 mg/kg, 15.6 mg/kg, and 31.2 mg/kg) and control groups of BALB/C mice were distributed at random. To evaluate roxadustat's anti-hypoxic effectiveness at the recommended dose, an atmospheric pressure closed hypoxic experiment was used. Wistar rats were randomly assigned to groups that received normal oxygen, hypoxic, acetazolamide, or roxadustat in order to evaluate the protective effects against hypoxic damage. Animal blood was obtained for arterial blood-gas analysis, inflammatory factors, and the identification of oxidative stress indicators. Animal tissues were removed for pathological investigation.Results: In each group, the mice's survival time was noticeably extended compared to the normal oxygen group. The medium dose had the best time extension rate at 19.05%. Blood SatO2 and PaO2 were significantly higher in the roxadustat group compared to the hypoxic group. Erythrocyte content, hemoglobin content, and hematocrit were also significantly higher. Plasma levels of IL-6, TNF-α, and IFN-γ were also significantly lower in the roxadustat group. Roxadustat can also improve the level of oxidative stress in the tissues of hypoxic rats. According to the results of HE staining, roxadustat could greatly lessen the harm done to rat heart, brain, lung, liver, and kidney tissue as a result of hypoxia.Conclusion: Roxadustat can greatly reduce inflammation, oxidative stress, and tissue damage brought on by hypoxia, showing that it can significantly enhance the body's ability to adapt to high altitude exposure.Keywords: roxadustat, high altitude, hypoxia, pharmacodynamics, erythrocyte